History and Phenomenology of Islamic Education in Mualaf Villages - Syamsuddin, Syamsuddin (Khalifa Journal of Islamic Education, 2022)
The study was to analyze the driving factors of one's entry into Islam (muallaf), and the development of education in those "converted" communities. The study was conducted using qualitative methods with a phenomenology approach in lapela village of the spooky eastern Province of Maluku, Indonesia. The data sources were taken using individual interviews of sixteen informers made up of the people, the people, the customs, the religious leaders, and the people living in the mualaf village. To supplement the interviews, the authors also made four-month live observations at the research site. All data of the interview and thematically analyzed observations are using NVivo 12 software. As a whole, the findings suggest, that one: of the six factors leading to mass conversion: i) (the living, ii) self-interest, iii)) conflict between religions, v) the role of religious leaders, and vi) the teaching of Islam is easily studied and understood by society. Second; Associated with educational phenomena are found four problematic societies studying Islamic religion: i) lack of competence and knowledge of educators, ii) inadequate means and infrastructure, iii), low levels of people's economy and iv) geographic conditions that resulted in limited access to religious activities. The results of this study can be used as the preliminary data for later researchers to examine the problem in different contexts and issues.